2017
DOI: 10.1080/21645515.2017.1342021
|View full text |Cite
|
Sign up to set email alerts
|

Open-label phase I clinical trial of Ad5-EBOV in Africans in China

Abstract: The application of Ad5-EBOV demonstrated safe in Africans in China and a specific GP antibody and T-cell response could occur 14 d after the first immunization. This acceptable safety profile provides a reliable basis to proceed with trials in Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…Members of this species cause a significant proportion of acute respiratory tract infections in children [179,180]. Despite widespread pre-existing immunity, HAdV-C5 vectors are currently being used as vaccine platforms in many countries, principally against HIV [181,182], malaria [183,184,185], Ebola virus [186,187,188,189,190], influenza virus [191], tuberculosis [192,193], or in pre-clinical studies that are targeting Zika virus [194,195], Clostridium botulinum [196], type O foot-and-mouth disease virus [197], Middle East respiratory syndrome coronavirus [198,199], rabies virus [200,201], or Dengue virus [202]. In mice and NHPs, HAdV-C2 delivered antigens protected against Ebola virus [203].…”
Section: S and 1960s: Hadvs Etiology And Pathogenicitymentioning
confidence: 99%
“…Members of this species cause a significant proportion of acute respiratory tract infections in children [179,180]. Despite widespread pre-existing immunity, HAdV-C5 vectors are currently being used as vaccine platforms in many countries, principally against HIV [181,182], malaria [183,184,185], Ebola virus [186,187,188,189,190], influenza virus [191], tuberculosis [192,193], or in pre-clinical studies that are targeting Zika virus [194,195], Clostridium botulinum [196], type O foot-and-mouth disease virus [197], Middle East respiratory syndrome coronavirus [198,199], rabies virus [200,201], or Dengue virus [202]. In mice and NHPs, HAdV-C2 delivered antigens protected against Ebola virus [203].…”
Section: S and 1960s: Hadvs Etiology And Pathogenicitymentioning
confidence: 99%
“…However, it was found that pre-existing anti-HAd5 antibodies which are present in a large proportion of the human population could significantly dampen the humoral and cellular immune response to the vaccine antigen. 25 Various strategies have since been explored to circumvent this problem: the use of alternative human serotypes, such as HAd26 or HAd35, 26 re-engineering the capsid of HAd5 to prevent antibody recognition, 27 and the use of simian adenoviral vectors against which there is no pre-existing immunity. 28 As discussed above, chimpanzee adenoviral vectors (ChAds) have successfully been used in clinical trials against a variety of diseases.…”
Section: Progression Of the Vectored Vaccine Approach: Success Of Rapmentioning
confidence: 99%
“…128,129 Nonreplicating Viral Vectorebased Vaccines Human Ad5 was used for some early viral vector vaccines, but the cellular and humoral immune responses to vaccine inserts were inhibited by preexisting neutralizing antibodies to the vector. 130 To overcome this challenge, researchers shifted to vectors based on other serotypes with lower seroprevalence, such as Ad26 and Ad35, 131 chimeric forms of adenovirus to prevent immune recognition (Ad5H3) using the antigen capsid-incorporation technique, 132 and the chimpanzee-adenovirus vector to which most humans have not been previously exposed. 133 In the antigen capsideincorporation strategy, chimeric Ad5H3 was created by adding a polyhistidine sequence (His 6 ) into the hexon3 (H3) capsid protein of Ad5.…”
Section: Dna-based Vaccinesmentioning
confidence: 99%